'Happier in My Lonely Cell': Convict Women's Textiles. (3rd July 2022) - Hughes, Helen
Abstract: This article concerns the near total lack of artworks by Australia's convict women that have come to light. First, I examine the reasons why convict women's art was either not produced or not preserved, and then I offer a preliminary analysis of three textile artworks made by convict women in the mid-nineteenth century: the exceedingly well known Rajah Quilt (1841) and two less well known embroidery samplers from around the same time. In comparing these textiles, this article articulates the complex status of so much convict art regardless of its maker's gender: its oscillation between a form of creative self-expression and an exercise in strict disciplinary reform and social conditioning from above. Yet, this article also shows how sexual difference inflected the life-worlds of female convicts and the textile art they produced, focusing on the gendered productive and reproductive forms of labour that were demanded of convict women in the penal colonies of Australia.